A Rare Cause of Spontaneous Pneumothorax. Issue 4 (July 2019) - Cartin-Ceba, Rodrigo; Jokerst, Clinton E.; Jensen, Eric A.; Cummings, Kristopher W.; Gotway, Michael B.
Abstract : Pulmonary nodules detected at thoracic imaging studies are a frequent occurrence. The management of such nodules largely revolves around comparison with prior imaging studies to document stability, and, in the absence of such priors, serial imaging assessment, as determined by the patient's age, smoking status, and nodule characteristics, including size, border characteristics, and nodule attenuation. Often such incidentally detected nodules, particularly when small, are ultimately shown to be benign through lack of growth at serial imaging assessment, and therefore a conservative approach to these nodules is generally favored. In contrast, larger solid nodules, particularly when >1 cm in size, or cavitation within a nodule, herald a potentially more aggressive, or even an "active, " process that frequently warrants definitive evaluation. Although the differential diagnosis of solid nodules and cavitary nodules is similar, the presence of cavitation often specifically raises the possibility of active infection or malignancy. In addition, the presence of cavitation within a nodular pulmonary opacity can be seen with a number of noninfectious, inflammatory lesions that are treated substantially differently than either infection or malignancy, and therefore definitive diagnosis is usually required in these circumstances. Finally, cavitary lung disorders can result in complications, including spontaneous pneumothorax, hemopneumothorax, pyothorax, and even bronchopleural fistula.